Identification of compounds in Garcinia kola (Heckel) Fruit Pulp Using Gas Chromatography-Mass Spectrometry - , Nuria Chinonyerem Amaechi; , Uchenna Okonkwo (Archives of Current Research International, 2017)
Garcinia kola fruit pulp is consumed by few human populations as food for its medicinal usefulness. The aim of this work was to identify compounds in dichloromethane/methanol and methanol extracts of G. kola fruit pulp using Gas Chromatography-Mass Spectrometry analysis. Twenty eight bioactive compounds were identified in the dichloromethane/methanol extract while thirty eight compounds were identified in the methanol extract. The most abundant compounds in the methanol extract were 3-Methyl-2,5-furandione, 5-hydroxymethyl furfural and 4,5-diethenyl-2,2-dimethyl-1,3-dioxolane which had concentrations of 17.37%, 14.53% and 10.55% respectively. The most abundant compounds in the dichloromethane/methanol extract were lupeol, n- hexadecanoic acid (i.e palmitic acid) and (Z) Octadec-9-enoic acid (i.e oleic acid) which had concentrations of 37.53%, 12.94% and 10.24% respectively. Results indicated that polarity of the solvents used in extraction influenced the relative abundance and type of compounds extracted. Various compounds identified are known to have varying bioactivities such as being anticancer, antioxidant and anti-sickling. Therefore the presence of these compounds in Garcinia kola fruit pulp could be useful in the preparation of functional foods and neutraceuticals in preventing and treating debilitating and chronic human diseases.